PROGRESSIVE MYOCLONUS-ATAXIA SYNDROMES: DIAGNOSTIC CHALLENGES AND PRACTICAL APPROACHES - Karolina Wojdat-Krupa; Karol Sikora; Paulina Lewaśkiewicz; Filip Lachowski; Martyna Wasyluk; Paweł Jan Babiński; Anita Jalali (International Journal of Innovative Technologies in Social Science, 2025)
Background: Progressive myoclonus-ataxia syndromes (PMAs) are a heterogeneous group of rare neurological conditions characterized by the coexistence of myoclonus and cerebellar ataxia, frequently associated with epilepsy and cognitive decline. Their rarity, phenotypic overlap, and genetic variability create major diagnostic difficulties.Aim: This article provides a narrative review of the principal PMA syndromes, emphasizing clinical features, diagnostic strategies, and management options.Methods: A narrative review of PubMed and Embase publications (2013–2023), supplemented with earlier landmark studies, was conducted. The review highlights diagnostic algorithms and therapeutic approaches across the PMA spectrum.Results: Classic syndromes include Unverricht–Lundborg disease, Lafora disease, sialidosis, neuronal ceroid lipofuscinoses, North Sea progressive myoclonus epilepsy (GOSR2), and mitochondrial disorders (MERRF, MELAS). Key diagnostic clues involve age of onset, epilepsy phenotype, ophthalmologic findings, and neuroimaging. Next-generation sequencing has revolutionized diagnostic precision, although accessibility remains a challenge.Conclusion: Early recognition of PMAs improves patient management and avoids harmful therapies. A structured diagnostic approach is essential, and recent developments in molecular genetics and enzyme replacement provide hope for future targeted interventions.